Intradural Extension of a Pyogenic Epidural Abscess: A Case Report. Issue 3 (July 2015) - Rosinsky, Philip J.; Zimhony, Oren; Ciobotaro, Pnina; Sagiv, Shaul; Ben-Galim, Peleg
Abstract : Case: Few cases of spinal epidural abscess involving an extradural abscess with an intradural extension have been reported. A unique complication with extension of pus from the epidural space through multiple perforations into the dura is described. Due to a proximal meningeal inflammatory reaction, which served as a proximal plug, no cerebrospinal fluid leak was encountered. Conclusion: Intradural extension of pus through multiple dural perforations is a rare complication of spinal epidural abscess and a treatment challenge. Early diagnosis enabling prompt surgical decompression, along with subsequent aggressive debridements and prolonged intravenous antibiotic treatment, can lead to a favorable outcome.